2020
DOI: 10.21203/rs.3.rs-45498/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Virtual Consultations in Plastic Surgery During COVID-19

Abstract: Background: COVID-19 has led to government enforced ‘lockdown’ in the UK severely limiting face-to-face patient interaction. Virtual consultations present a means for continued patient access to healthcare. Our aim was to evaluate the use of virtual consultations (VCons) during lockdown and their possible role in the future. Methods: An anonymous survey was disseminated to UK and European plastic surgeons via social media, email sharing and, via the EASAPS (European Association of Societies of Aesthetic Plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A number of data breaches occurred in the first half of 2020 [49], with access of personal data featuring in all ten highlighted cases. A survey of 43 senior plastic surgeons [50] elicited their views on the future of virtual consultations in plastic surgery; 38% of respondents were not aware of encryption and 48% were unaware of GDPR compliance. As the number of remote consultation platforms grow, it is essential that patients and clinicians are aware of their potential security issues and that policies and procedures reflect increased risks [51].…”
Section: Security Issuesmentioning
confidence: 99%
“…A number of data breaches occurred in the first half of 2020 [49], with access of personal data featuring in all ten highlighted cases. A survey of 43 senior plastic surgeons [50] elicited their views on the future of virtual consultations in plastic surgery; 38% of respondents were not aware of encryption and 48% were unaware of GDPR compliance. As the number of remote consultation platforms grow, it is essential that patients and clinicians are aware of their potential security issues and that policies and procedures reflect increased risks [51].…”
Section: Security Issuesmentioning
confidence: 99%
“…Specifically, the software recommended in the implementation phase within the illustrated document is Skype™ [13], as it is free and widely accessible throughout the country. Numerous studies and international scientific experiences have demonstrated the validity of this platform in healthcare settings, having been applied for various purposes with encouraging results: virtual rehabilitation interventions for language disorders, remote synchronous consultations in Ophthalmic Telesurgery, health status monitoring following different kinds of interventions, psychotherapy, virtual consultations in Plastic Surgery, as well as in several clinical settings [14][15][16][17][18][19][20][21][22]. The choice of the platform is therefore based on the evidence of its validity, cost, and widespread availability within the territory.…”
mentioning
confidence: 99%